Pengaruh Transfer Pricing dan Risk Governance terhadap Tax Aggressiveness yang Dimoderasi oleh Financial Distress - Rizqah Hanie Pratiwi; Vinola Herawaty (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Rapid growth in the global business environment has led companies to engage in cross-border activities, including transfer pricing. This phenomenon is becoming increasingly complex with the existence of independent commissioners and audit committees as key elements in maintaining the integrity and transparency of the company. Meanwhile, tax aggressiveness is the main concern in maintaining corporate tax compliance. The purpose of this study is to determine the influence of Transfer Pricing, Board Size, Board Meeting, Risk Committee Size, and Risk Committee Meeting on Tax Aggressiveness with Financial Distress as a moderation variable. The research object used in this study is companies with the Consumer Non-Cyclicals sector listed on the IDX in 2021-2023. The number of samples used in the study was 125 data samples. The results of this study show that Financial Distress cannot moderate the influence of transfer pricing, board size, risk committee, and risk committee meeting on tax aggressiveness. Other results show that financial distress is able to weaken the negative influence of board meetings on tax aggressiveness.